Loopholes in Law: Why Local Strategies Fail to Curb Child Marriage in Jember Regency - Muslifah, siti; Rosyid, Muhammad Aenur; Arfan, Iklil Athroz (Sakina: Journal of Family Studies, 2025)
In the last three years, the rate of early marriage in Jember Regency has been quite high, and in 2023 it ranked first in East Java. Raising the minimum age limit for prospective female brides has not been able to reduce child marriage rates because it can still be circumvented through dispensation applications. Therefore, synergy between relevant stakeholders is needed, especially the role of the Jember Regency government in reducing early marriage to create a child-friendly Jember Regency. The purpose of this research is to understand community perceptions of the high rate of early marriage in Jember Regency, analyze government efforts to prevent early marriage, and measure the legal effectiveness of the implemented measures. This research uses qualitative methods with a sociological juridical approach. The results of this research are as follows. First, according to community perceptions, the high rate of early marriage in Jember Regency is influenced by several factors such as parents' economic problems, low education levels, arranged marriage culture leading to early marriage, parents' culture of indebtedness to their helpers, engagement customs conducted simultaneously with unregistered (sirri) marriage ceremonies, parents' concerns about their daughters being stigmatized as unmarriageable, pregnancy outside marriage, and misinterpretation of religious teachings. Second, Jember Regency Government's efforts to reduce early marriage rates through Circular Letter Number 474/196/35.09.317/2024 concerning dispensation application services. Third, from the perspective of legal effectiveness theory, the Jember Regency government's efforts to reduce early marriage rates have not been effective because the Jember Regency government only issues a Regent's Circular Letter regulating administrative requirements for marriage dispensation applications, which has a weak legal position and is easily circumvented by the community.